2020
DOI: 10.4143/crt.2019.598
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Immune Checkpoint Blocker Therapy for Malignant Melanoma in Korean Patients: Potential Clinical Implications for a Combination Strategy Involving Radiotherapy

Abstract: PurposeWe investigated the clinical efficacy of immune checkpoint blocker (ICB) therapy for metastatic or advanced melanoma in Korean patients. As well, we assessed whether the effects of ICBs can be enhanced by combination therapy with palliative radiotherapy (RT).Materials and MethodsWe retrospectively reviewed the records of 127 patients with metastatic melanoma who received ICB with or without palliative RT between 2014 and 2018. The melanoma subtypes were classified as follows: chronic sun-damaged (CSD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Immunological checkpoint inhibitions are one of the successful therapeutic approaches during malignancies ( Lee et al, 2020 ). Recent reports revealed the positive effects of immunotherapy for patients suffering from cancer where therapies associated with immune checkpoint inhibitors like programmed death-ligand 1 (PD-L1) inhibitor or anti-programmed death-1 receptor (PD-1) ( Park et al, 2019 ) (see Fig.…”
Section: Present Day Standard Therapeutics In Gastric Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Immunological checkpoint inhibitions are one of the successful therapeutic approaches during malignancies ( Lee et al, 2020 ). Recent reports revealed the positive effects of immunotherapy for patients suffering from cancer where therapies associated with immune checkpoint inhibitors like programmed death-ligand 1 (PD-L1) inhibitor or anti-programmed death-1 receptor (PD-1) ( Park et al, 2019 ) (see Fig.…”
Section: Present Day Standard Therapeutics In Gastric Cancermentioning
confidence: 99%
“…Despite several attainments in immune-checkpoint-blockade (ICB) to cure cancer, there are a few effective anticipating biomarkers in gastric cancer ( Lee et al, 2020 ). The functioning of two biomarkers of CNA (copy-number alterations) burden and TMB (tumor mutational burden) may help DCB (durable clinical benefit) patients grouping, thus giving a logical option for patients medicated with immune checkpoint blockade ( Lee et al, 2020 ). However, forecasting tumor reaction to PD‐1 blockade still remains complicated ( Ishikawa et al, 2018 ).…”
Section: Present Day Standard Therapeutics In Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The response rates for ipilimumab and pembrolizumab or nivolumab range from 11-19% [5,7] and 33-44% [2,5,6], respectively. We have previously reported that the objective response rate of ICB monotherapy in South Korean patients with melanoma is 15% [8].…”
Section: Introductionmentioning
confidence: 99%
“…The response rates for ipilimumab and pembrolizumab or nivolumab range from 11% to 19% ( 5 , 7 ) and 33% to 44% ( 2 , 5 , 6 ), respectively. We have previously reported that the objective response rate of ICB monotherapy in South Korean patients with melanoma is 15% ( 8 ).…”
Section: Introductionmentioning
confidence: 99%